Disruption of KMT2D perturbs germinal center B cell development and promotes lymphomagenesis - Zhang, Jiyuan (Nat Med, 2015)
Mutations in the gene encoding the KMT2D (also called MLL2) methyltransferase are highly recurrent and occur early during tumorigenesis in diffuse large B cell lymphoma (DLBCL) and follicular lymphoma (FL). However, the functional consequences of KMT2D mutations and their role in lymphomagenesis are unknown. Here we show that FL/DLBCL-associated KMT2D mutations impair KMT2D enzymatic activity, leading to diminished global H3K4 methylation in germinal-center (GC) B-cells and DLBCL cells. Conditional deletion of Kmt2d early during B cell development, but not after initiation of the GC reaction, results in an increase in GC B-cells and enhances B cell proliferation in mice. In mice overexpressing BCL2, which develop GC-derived lymphomas resembling human tumors, genetic ablation of Kmt2d leads to a further increase in tumor incidence. These findings suggest that KMT2D acts as a tumor suppressor gene whose early loss facilitates lymphomagenesis by remodeling the epigenetic landscape of the cancer precursor cells. Eradication of KMT2D-deficient cells may represent a rational therapeutic approach for targeting early tumorigenic events.